2018
DOI: 10.1007/s11302-018-9606-7
|View full text |Cite
|
Sign up to set email alerts
|

Intralesional uridine-5′-triphosphate (UTP) treatment induced resistance to Leishmania amazonensis infection by boosting Th1 immune responses and reactive oxygen species production

Abstract: Leishmania amazonensis is the etiologic agent of cutaneous leishmaniasis, an immune-driven disease causing a range of clinical symptoms. Infections caused by L. amazonensis suppress the activation and function of immune cells, including macrophages, dendritic cells, and CD4 T cells. In this study, we analyzed the course of infection as well as the leishmanicidal effect of intralesional UTP treatment in L. amazonensis-infected BALB/c mice. We found that UTP treatment reduced the parasitic load in both footpad a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 42 publications
(61 reference statements)
1
11
0
Order By: Relevance
“…We recently reported that UTP-intralesional treatment elicited a Th 1 immune response in an experimental model of cutaneous leishmaniasis [ 21 ], suggesting the involvement of P2Y 2 R. Here, we evaluated whether the intralesional treatment with a selective P2Y 2 R agonist (2-thio-UTP) would promote L. amazonensis control in BALB/c mice. As shown in Figure 1(a) , tissues were harvested for analysis at 26 d.p.i.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently reported that UTP-intralesional treatment elicited a Th 1 immune response in an experimental model of cutaneous leishmaniasis [ 21 ], suggesting the involvement of P2Y 2 R. Here, we evaluated whether the intralesional treatment with a selective P2Y 2 R agonist (2-thio-UTP) would promote L. amazonensis control in BALB/c mice. As shown in Figure 1(a) , tissues were harvested for analysis at 26 d.p.i.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported the involvement of purinergic receptors, including P2Y 2 R and P2X7R, in the control of L. amazonensis infection in vitro and in vivo [ 4 , 19 ]. These receptors induce the activation of several microbicidal mechanisms in host cells during infection (i.e., NO, ROS, LTB 4 production) [ 20 , 21 , 26 , 27 ]. Here, we identified a protective mechanism triggered by P2Y 2 R, using incubation with either a specific agonist for P2Y 2 R, 2-thio UTP, or low concentrations of UTP (100 μ M) or ATP (50 μ M) during in vitro infection with L. amazonensis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, we showed that ATP secreted after cell lysis can control the survival of the protozoan parasites Plasmodium chabaudi and Toxoplasma gondii ( 24 , 25 ), in a mechanism involving ROS production ( 26 ). We also showed that Leishmania amazonensis infection positively modulates the expression of P2X7, P2Y 2 , and P2Y 4 receptors in macrophages ( 19 , 20 ), and that the activation of P2 receptors by nucleotide secretion is likely to represent a physiological mechanism for parasitism control ( 5 ), since UTP and ATP have crucial roles in restraining the proliferation of L. amazonensis ( 19 , 20 , 27 ). P2X7 receptor activation induces resistance to L. amazonensis infection in macrophages, via a mechanism involving LTB 4 production ( 5 ).…”
Section: Introductionmentioning
confidence: 73%
“…Our group has been reporting the involvement of extracellular nucleotides such as UTP and ATP in restraining the replication of L. amazonensis ( 5 , 19 , 20 , 27 ). Recent evidence suggests that the presence of ATP in the extracellular environment can trigger further ATP release for different human cell types—including leukocytes, urothelial cells, osteocytes, neutrophils, and macrophages ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%